A potent free fatty acid receptor 1 agonist with a glucose-dependent antihyperglycemic effect. Issue 61 (10th July 2019) - Wang, Xuekun; Xu, Yurui; Feng, Shujun; Huang, Xinyu; Meng, Xia; Chen, Jiao; Guo, Leilei; Ge, Junliang; Zhang, Jikang; Chen, Jianmei; Cheng, Li; Gu, Kai; et al.
Abstract : PAFA is a promising free fatty acid receptor 1 agonist with a glucose-dependent antihyperglycemic effect, allowing for treating type-2 diabetes. Abstract : We present a novel free fatty acid receptor 1 (FFA1) agonist, named PAFA, with a strong agonist potency (EC50 = 6.04 nM) and good serum stability. PAFA significantly stimulates insulin secretion in INS-1 cells in a glucose-dependent manner and exhibits high antihyperglycemic effects in db/db mice without adverse effects.